COVID-19 TERMINOLOGIES: THE EXTENT OF STUDENT’S VOCABULARY ACQUISITION DURING LEARNING FROM HOME - I Nyoman Suparsa; Ida Bagus Nyoman Mantra (International Journal of Linguistics and Discourse Analytics, 2020)
The coronavirus pandemic has affected the lives of people across the globe which forced students to work from home. In the education sector, students are strongly suggested to stay home and study from home. Consequently, online learning becomes a necessary learning process during the outbreak of COVID-19. Students are expected to be active in engaging themselves in learning. Suddenly they are confronted with many terminologies concerning classroom interaction. Many students found some of the terminologies confusing. This study was intended to find out the students' acquisition of COVID-19 terminologies which are commonly used in classroom interaction. The study found that students have inadequate comprehension of COVID-19 terminologies although they are widely exposed to terminologies in their daily life. Only common terminologies were comprehended appropriately. This study implies that a learning program should be provided to improve students' acquisition of COVID-19 terminologies